2008
DOI: 10.1128/jcm.02343-07
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric Assay for Testing Rifampin Susceptibility of Mycobacterium tuberculosis Complex

Abstract: The emergence and transmission of multidrug-resistant tuberculosis (MDR-TB) and extensively drugresistant tuberculosis (XDR-TB) have raised concern about diagnostic delay associated with culture-based drug susceptibility testing methods. The association between rifampin resistance and MDR-TB or XDR-TB makes it an important genetic marker for genotypic drug susceptibility testing. In this article, we describe the analysis of the physical properties of the rifampin resistance-determining region (RRDR) in the rpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…Second, mutations within the RRDR of rpoB have been reported to occur in 95% or higher of the RIF-resistant isolates (9,36,54). Third, RIF resistance is an excellent surrogate marker for MDR M. tuberculosis (26,37). In the present study, six novel rpoB mutations were identified, and they all fell outside of the RRDR region of the rpoB gene.…”
Section: Discussionmentioning
confidence: 71%
“…Second, mutations within the RRDR of rpoB have been reported to occur in 95% or higher of the RIF-resistant isolates (9,36,54). Third, RIF resistance is an excellent surrogate marker for MDR M. tuberculosis (26,37). In the present study, six novel rpoB mutations were identified, and they all fell outside of the RRDR region of the rpoB gene.…”
Section: Discussionmentioning
confidence: 71%
“…Melting of the PCR product is also influenced by various factors, such as salt in the buffer solution, DNA quality, DNA concentration and DNA extraction methods, along with other factors that can influence the behaviour of the melting curves. A previous study suggested another twostep HRMA technique that alters the shape of the melting transition to increase the sensitivity and specificity by forming heteroduplexes (Hoek et al, 2008). This two-step technique may in fact cause cross-contamination and may be cumbersome.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a differentiation by a single PCR step may be achieved through the addition of a reference DNA or of unlabeled probes (spiking) to the reaction, which will form heteroduplex amplicons that might exhibit differentiable HRM curve profiles. 23,31,32 In conclusion, mutation scanning by HRM curve analysis of a 500-bp inlB fragment identified the clinically most relevant L. monocytogenes serotypes and enabled rapid, reliable, simple, and cost-effective typing of L. monocytogenes. Application of this technique differentiated 15 HRM subtypes and enabled the analysis of 384 samples in less than 2 hours using an LightCycler 480 instrument.…”
Section: Discussionmentioning
confidence: 86%